Pengembangan Media Pembelajaran EMI-PPKN Berbasis Digital Tematik Kelas V Sekolah Dasar - Mega Santi; Rury Rizhardi; Noviati Noviati (SCHOLASTICA JOURNAL JURNAL PENDIDIKAN SEKOLAH DASAR DAN PENDIDIKAN DASAR (Kajian Teori dan Hasil Penelitian), 2024)
Abstract: The development of thematic digital-based EMI-PPKN learning media for class V elementary schools, has the aim of knowing the development of valid and practical EMI-PPKN products. The type of research used by researchers in developing EMI-PPKN is R&D (Research and Development), development using the ADDIE model consisting of Analysis, Design, Development, Implementation, Evaluation. The subjects of this research were students in classes V.A and V.B at state elementary school 95 Palembang with a total of 35 students. The data collection techniques used in the research are observation, interviews, questionnaires, based on the results of research by validator experts from three fields, namely media, materials and language, where in this development there are 3 validators covering these 3 fields, so that the percentage of validators from the three experts is 90.83 % categorized as "Very Valid". Then the practicality test of the teacher's response obtained a percentage result of 86.66% categorized as "Very practical", then the one to one (Individual) trial obtained a percentage of 93.88% categorized as "Very practical", then the final trial, namely the small group, received a score percentage of 91.88% in the "Very practical" category. Keywords: Learning Media Development, EMI-PPKN, Digital